ANALISIS DAMPAK PENURUNAN PARTISIPASI PETANI MUDA, TINGKAT PEMANFAATAN TEKNOLOGI DIGITAL DAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Putri Inaya Ahmad; Boby Rantow Payu; Rifi Fazrina Djuuna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of young farmers’ participation, the utilization of digital technology, and the level of education on the economic growth of the agricultural sector in Indonesia. The study employed a quantitative approach using cross-sectional data from 34 provinces in Indonesia in 2023. The dependent variable in this study was the economic growth of the agricultural sector, measured by the Gross Regional Domestic Product (GRDP) of the agricultural sector at constant prices. The independent variables consisted of the ratio of young farmers aged 19–39 years, the ratio of digital technology utilization by young farmers, and the average years of schooling. The analysis technique used was multiple linear regression with the assistance of Stata software.The results showed that the participation of young farmers had a negative and significant effect on the economic growth of the agricultural sector in Indonesia. The utilization of digital technology had a positive effect on agricultural economic growth. In addition, the average years of schooling had a negative and significant effect on the economic growth of the agricultural sector. Simultaneously, young farmers’ participation, digital technology utilization, and education level significantly affected the economic growth of the agricultural sector in Indonesia. These findings indicate that improving the quality of agricultural human resources through the regeneration of young farmers, strengthening digital technology adoption, and enhancing education are important factors in promoting sustainable economic growth in Indonesia’s agricultural sector.